Electrocatalysis degradation of coal tar wastewater using a novel hydrophobic benzalacetone modified lead dioxide electrode. (February 2022) - Yu, Naichuan; Wei, Jingyu; Gu, Zhensheng; Sun, Hailong; Guo, Yong; Zong, Jun; Li, Xi; Ni, Pan; Han, Enshan
Abstract: Coal tar wastewater is hard to degrade by traditional methods because of its toxic pollutant constituents and high concentration of aromatic hydrocarbons, especially phenolic substances. A new type of hydrophobic benzacetone modified PbO2 anode (BA-PbO2 electrodes) was used for the electrocatalytic treatment of coal tar wastewater in a continuous cycle reactor. The surface morphology, structure, valences of elements, hydrophobicity, hydroxyl radical (·OH) produced capacity, electrochemical properties and stability of BA-PbO2 electrodes were characterized by SEM (scanning electron microscopy), XRD (X-ray diffraction), XPS (X-ray photoelectron spectroscopy), contact angle, a fluorescence probe test, an electrochemical workstation and accelerated life test, respectively. The BA-PbO2 electrodes exhibited a compact structure and finely dispersed crystallize size of 4.6 nm. The optimum degradation conditions of coal tar wastewater were as follows: current density of 90 mA cm −2, electrode gap of 1 cm and temperature at 25 °C with flow velocity of 80 L h −1 . The chemical oxygen demand (COD) removal efficiency reached 92.39% after 240 min of degradation under the optimized conditions and the after-treatment COD value was 379.51 mg L −1 which was lower than the centralized emission standard (less than 400 mg L −1 ). These findings demonstrated the feasibility and efficiency of electrocatalytically degrading coal tar wastewater by BA-PbO2 electrodes. The possible mechanism and pathway for phenol a specific pollutant in coal tar wastewater were investigated by quantum chemistry calculations (Multiwfn) and gas chromatography-mass spectrometry (GC-MS). The toxicity of each intermediate was predicted by the ECOSAR program. Graphical abstract: Image 1 Highlights: A novel hydrophobic PbO2 electrode was fabricated and characterized. BA-PbO2 electrode effectively remove phenol from actual coal tar wastewater. Degradation pathways and ecotoxicity were revealed systematically. Fukui functions and dual descriptor were calculated to predict reactive sites. A novel continuous cycle reactor was used in the degradation system.